Frontotemporal dementia is the leading cause of "true" A−/T+ profiles defined with Aβ42/40 ratio. Issue 1 (15th February 2019) - Pouclet‐Courtemanche, Hélène; Nguyen, Tri‐Bao; Skrobala, Emilie; Boutoleau‐Bretonnière, Claire; Pasquier, Florence; Bouaziz‐Amar, Elodie; Bigot‐Corbel, Edith; Schraen, Susanna; Dumurgier, Julien; Paquet, Claire; Lebouvier, Thibaud
Abstract: Introduction: Patients with positive tauopathy but negative Aβ42 (A−T+) in the cerebrospinal fluid (CSF) represent a diagnostic challenge. The Aβ42/40 ratio supersedes Aβ42 and reintegrates "false" A−T+ patients into the Alzheimer's disease spectrum. However, the biomarker and clinical characteristics of "true" and "false" A−T+ patients remain elusive. Methods: Among the 509 T+N+ patients extracted from the databases of three memory clinics, we analyzed T+N+ patients with normal Aβ42 and compared "false" A−T+ with abnormal Aβ42/40 ratio and "true" A−T+ patients with normal Aβ42/40 ratio, before CSF analysis and at follow‐up. Results: 24.9% of T+N+ patients had normal Aβ42 levels. Among them, 42.7% were "true" A−T+. "True" A−T+ had lower CSF tau P181 than "false" A−T+ patients. 48.0% of "true" A−T+ patients were diagnosed with frontotemporal lobar degeneration before CSF analysis and 64.0% at follow‐up, as compared with 6% in the "false" A−T+ group ( P < .0001). Discussion: Frontotemporal lobar degeneration is probably the main cause of "true" A−T+ profiles. Highlights: Dementia with normal cerebrospinal fluid Aβ42 yet high cerebrospinal fluid tau 181P is a situation referred to as A−T+N+ in the 2018 National Institute of Aging–Alzheimer's Association research framework. The interpretation of A−T+N+ profiles is not consensual and uncomfortable for clinicians. The use of Aβ42/40 ratio as a surrogate amyloid marker halves the number of uninformative A−T+N+ profiles. T+N+ patients with normal Aβ42 yet abnormal Aβ42/40 have an Alzheimer's phenotype. Frontotemporal lobar degeneration is probably the leading cause of A−T+N+ profiles.